THE RELATIONSHIP BETWEEN PHYSICAL REALITY AND AUGMENTED/VIRTUAL REALITY IN TOURISM: THE QUEST FOR SPECIAL RESTAURANTS - Erika KULCSÁR; Judit Tímea INCZE; Gabriella TAMÁS (Management & Marketing)
There is no area in economy that technology has not tried to rewrite, or at least has started to change it so far. The tourism is an area where the presence of technology is very varied, even up to the extremities. The spectrum is very wide in this respect: from simple online reservation to augmented reality (AR) or even to virtual reality (VR), technology is represented in various forms in tourism. The extent of the technology's presence in the tourism product typically depends on the target segment. In this respect, the changes or trends of the consumers must be constantly monitored. The present study aims (a) to sum up what AR/VR in tourism means, (b) identification of physical forms (physical environments) of certain restaurants and their evaluation by the guests, (c) the role of AR/VR on the level of the marketing mix of the restaurants. In order for restaurant managers to market the positive outcome of the augmented or virtual reality, they must first build the physical environment in such a way as to enable this (technological) achievement to be exploited.